Courses
Courses for Kids
Free study material
Free LIVE classes
More # Evaluate $6 - 8 - ( - 6) \div 2$.

Last updated date: 28th Mar 2023
Total views: 207.3k
Views today: 2.86k Verified
207.3k+ views
Hint: Here we have a simple algebraic expression, we need to simplify it by applying the given operations. That is addition, subtraction, division and multiplication. To solve this we follow the BODMAS rule. This rule states that when given an equation or expression, we should first calculate the brackets, then any order, then division, then multiplication, then addition and then subtraction.

Complete step by step solution:
Given,
$6 - 8 - ( - 6) \div 2$
By BODMAS rule we simplify the brackets,
$\Rightarrow 6 - 8 + 6 \div 2$
Now we need to simplify the division part,
$\Rightarrow 6 - 8 + \dfrac{6}{2}$
$\Rightarrow 6 - 8 + 3$
$\Rightarrow 9 - 8$
Now subtracting
$\Rightarrow 1$
Thus the value of the algebraic expression is $6 - 8 - ( - 6) \div 2 = 1$.

Suppose they are given to simplify this $\left( {6 - 8 - ( - 6)} \right) \div 2$.
$\left( {6 - 8 + 6} \right) \div 2$
$\left( {12 - 8} \right) \div 2$
$\Rightarrow 4 \div 2$
$\Rightarrow 2$